2020
DOI: 10.31234/osf.io/8zycu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Synchronized Linked Band Selection on Speech Intelligibility of Bilateral Cochlear Implant Users

Abstract: Normal hearing listeners have the ability to exploit the audio input perceived by each ear to extract target information in challenging listening scenarios. Bilateral cochlear implant (BiCI) users, however, do not benefit as much as normal hearing listeners do from a bilateral input. In this study, we investigate the effect that bilaterally linked band selection, bilaterally synchronized electrical stimulation and ideal binary masks (IdBMs) have on the ability of 10 BiCIs to understand speech in background noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The results presented here agree with other work examining strategies aimed at improving binaural hearing outcomes. For example, Gajecki and Nogueira (2020) investigated the impact of synchronized stimulation and signal processing on speech in noise understanding. They found that both synchronized stimulation and signal processing were necessary to significantly improve SRM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented here agree with other work examining strategies aimed at improving binaural hearing outcomes. For example, Gajecki and Nogueira (2020) investigated the impact of synchronized stimulation and signal processing on speech in noise understanding. They found that both synchronized stimulation and signal processing were necessary to significantly improve SRM.…”
Section: Discussionmentioning
confidence: 99%
“…They found that both synchronized stimulation and signal processing were necessary to significantly improve SRM. It should be noted that the experimental condition in Gajecki and Nogueira (2020) is somewhat simpler than the one used in these experiments, where the masking talker was located on one side of the head. In this scenario, there is an ear with a significantly improved SNR, which means that the benefits of binaural listening such as squelch and summation might have been underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Linked spectral peak-picking did not significantly affect auditory motion discrimination, although some participants showed benefit (Dennison et al., 2019). In addition, some research suggests that linked spectral peak-picking improves speech understanding in spatially separated noise (Gajecki & Nogueira, 2020). A modeling study suggested that independent spectral peak-picking would negatively affect BiCI localization (Kelvasa & Dietz, 2015), and that independent processing could under some conditions cause stronger stimulation on contralateral electrodes and therefore create opposite-signed ILDs.…”
Section: Discussionmentioning
confidence: 99%
“…A non-peak-picking stimulation strategy such as CIS could serve this purpose, as could an experimentally linked peak-picking strategy (cf. Gajecki & Nogueira, 2020). Some evidence suggests that the different stimulation strategies implemented across CI manufacturers and devices may afford listeners varying localization performance (Killan et al., 2019), a result that could be further informed by future empirical recordings from a variety of devices.…”
Section: Discussionmentioning
confidence: 99%